Physical Activity and Recommendation for Heart Rate Recovery Treatment as an Endeavour in Community Health Education - Pramono, Bayu Agung; Mustar, Yetty Septiani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2019)
This research aim is to evaluate and educate people about the position selection in health recovery treatment for societies as well as athletes after doing physical activities. This is an experimental research design, these research activities are done through training, testing and evaluation of the heart rate on 16 teenagers (19 years old) who actively carry out physical activity at least 3-4 times a week, then divided into 4 groups each group will perform sub-maximum physical activities by using YMCA Step Test Protocol for three minutes. During physical activity, each group measured the heart rate exercise with different positions of standing, sitting, sleeping with feet above the heart (elevation) and sitting position while drinking water. In the next three minutes, after heart rate recovery treatment it found that the heart rate of exercise will decreased rapidly when using the sitting position while drinking water. With regard to this, it is imperative to consider health recovery position after having physical activity.